Healthy Foods as Proxy for Functional Foods: Consumers’ Awareness, Perception, and Demand for Natural Functional Foods in Pakistan - Akhter Ali; Dil Bahadur Rahut (International Journal of Food Science)
Using comprehensive primary dataset collected from 400 respondents from all four major provinces of Pakistan, this study assesses consumers’ knowledge, awareness, and perception regarding the use of functional foods. The empirical findings show that the majority of the consumers do not have information and knowledge about the functional foods in Pakistan. Hence, the frequency of consumption of functional food was low especially in rural areas. The result revealed that consumers with ill health were more eager to consume functional foods compared to healthier people. Besides health, the level of education and gender (female) of the respondent also play significant role in the acceptability and consumption of the functional foods in Pakistan. Geographically the people in the cities were more aware and willing to pay more for the functional foods as compared to people living in the villages. Majority of the consumers think that consumption of functional foods can help them to maintain good health, hence the policy makers’ needs to create more awareness.